Gaining insight by going in circles [neural control of human walking]. - Earhart, G.M.
Although most of us take it for granted, walking is actually a complex task that requires intricate neural control. Successful navigation through our changing daily environments requires the ability to adapt locomotor outputs to meet a variety of situations. For example, in order to walk around an obstacle or along a curve it is necessary to modify locomotor trajectory. The mechanisms at work in controlling locomotor trajectory are not well understood. One approach used to investigate these mechanisms is use of the rotating circular treadmill. The purpose of this article is to present an overview of this line of research. Topics discussed include: visual, vestibular, and somatosensory control of locomotor trajectory; the basics of podokinetic after-rotation (PKAR); and PKAR as a centrally mediated adaptive process or peripheral phenomenon. The questions are posed: Can PKR be obtained independently in one lower extremity and not the other? Does PKAR transfer from stepping to hopping? Does PKAR transfer from forward to backward walking? Is the cerebellum important for PKAR? PKAR appears to be an adaptive phenomenon that results from a remodeling of the rotational relationship between the trunk and the feet. Podokinetic adaptation is mediated, at least in part, by somatosensory information that is integrated within central nervous system structures. The cerebellum, in particular, is important in regulating the amplitude of this adaptive response.
Keywords: Adaptive response; Backward walking; Central nervous system structures; Centrally mediated adaptive process; Cerebellum; Changing daily environments; Curve; Feet; Forward walking; Hopping; Human walking; Locomotor outputs; Locomotor trajectory; Lower extremity; Navigation; Neural control; Obstacle; Peripheral phenomenon; Podokinetic adaptation; Podokinetic after-rotation.; Rotating circular treadmill; Rotational relationship; Somatosensory control; Somatosensory information; Stepping; Trunk; Vestibular control; Visual control